America's voucher politics : how elites learned to hide the state / Ursula Hackett. - Hackett, Ursula, 1988- (Cambridge University Press, 2020)
What explains the explosive growth of school vouchers in the last two decades? In America's Voucher Politics, Ursula Hackett shows that the voucher movement is rooted in America's foundational struggles over religion, race, and the role of government versus the private sector. Drawing upon original datasets, archival materials, and more than one hundred interviews, Hackett shows that policymakers and political advocates use strategic policy design and rhetoric to hide the role of the state when their policy goals become legally controversial. For over sixty years of voucher litigation, white supremacists, accommodationists, and individualists have deployed this strategy of attenuated governance in court. By learning from previous mistakes and anticipating downstream effects, policymakers can avoid painful defeats, gain a secure legal footing, and entrench their policy commitments despite the surging power of rivals. An ideal case study, education policy reflects multiple axes of conflict in American politics and demonstrates how policy learning unfolds over time.